Little known pages of biography and activities of professor S. Z. Katsenbogen (1889–1946) - Maksimchik, Andrey N. (Journal of the Belarusian State University. Sociology, 2019)
The article is devoted to the prominent Soviet sociologist and philosopher C. Z. Katsenbogen. On the basis of archival documents reveals its activity in the sphere of science and pedagogy in the post of deputy rector of the Belarusian State University and other Russian universities. Contains previously unknown facts of his biography and chronological list of his works.